Postcolonial Subjectivity in “Down Second Avenue” and “Women of Algeirs in Their Apartment” - Bekhal B. Kareem (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
The present research paper examines the concept of postcolonial subjectivity in two significant novels written by two different authors from different cultural backgrounds: Down Second Avenue by Ezekiel Mphalele in South Africa and Women of Algeries in Their Apartment by Assia Djebar in Algeria. The paper aims at the representation of the above mentioned concept through both the content and form of the chosen literary writings. It is hypothesized in this study that both authors have the intention to reconstruct the identity and history of their society. The basic findings this study arrives at are that both of the prominent authors failed in their trying of reforming their society because of the obstacles like racism and culture. Both of the novels have a dramatic conclusion in representation postcolonial subjectivity.